Development of a Cleaved Probe-Based Loop-Mediated Isothermal Amplification Assay for Rapid Detection of African Swine Fever Virus - Wang, Songqi; Shen, Haiyan; Lin, Qijie; Huang, Jun; Zhang, Chunhong; Liu, Zhicheng; Sun, Minhua; Zhang, Jianfeng; Liao, Ming; Li, Yugu; Zhang, Jianmin (Frontiers in Cellular and Infection Microbiology, 2022)
African Swine Fever (ASF), caused by African swine fever virus (ASFV), is a highly contagious and lethal viral disease of pigs. However, commercial vaccines are not yet available, and neither are drugs to prevent or control ASF. Therefore, rapid, accurate on-site diagnosis is urgently needed for detection during the early stages of ASFV infection. Herein, a cleaved probe-based loop-mediated isothermal amplification (CP-LAMP) detection method was established. Based on the original primer sets, we targeted the ASFV 9GL gene sequence to design a probe harboring a ribonucleotide insertion. Ribonuclease H2 (RNase H2) enzyme activity can only be activated when the probe is perfectly complementary, resulting in hydrolytic release of a quencher moiety, and consequent signal amplification. The method displayed robust sensitivity, with copy number detection as low as 13 copies/µL within 40 min at constant temperature (62C). Dual-mode visualization of the fluorescence product was employed using a self-designed 3D-printed dual function cassette, and the CP-LAMP method achieved specific identification and visual detection of ASFV. Moreover, coupling the dual function cassette and smartphone quantitation makes the CP-LAMP assay first user-friendly, cost-effective, portable, rapid, and accurate point-of-care testing (POCT) platform for ASFV.